Pengembangan Media Pembelajaran Fisika Berbantuan Edugame Untuk Meningkatkan Critical Thinking Skills Peserta Didik - Tariska Widiastuti; Umi Pratiwi; sriyono sriyono (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
Research has been carried out on the development of edugame-assisted physics learning media on android smartphones with the aim of determining the feasibility of the edugame-assisted learning media developed, increasing students' critical thinking skills, and the effectiveness of the media used in learning. The type of research used is development that refers to the ADDIE learning model, namely Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at MAN 3 Kebumen with 57 students as the test subject. The instruments used in the study were validation sheets, student response questionnaires, and critical thinking skills tests. Based on the research, data obtained from the validation results of edugame-assisted learning media from two expert validators got an overall score of 3.90 including the very valid category and suitable for use in learning. The improvement of students' critical thinking skills at the implementation stage in class X MIPA obtained an N-gain of 0.67 and was included in the medium improvement category. The effectiveness of the media used in learning is indicated by the student response questionnaire getting an overall percentage of 82.75% and is included in the very practical category. So that physics learning media assisted by edugame can be used as an alternative media in learning to help improve students' critical thinking skills.